2008
DOI: 10.1021/jp801620w
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Ozone with Solid Potassium Iodide Investigated by Atomic Force Microscopy

Abstract: The reaction of ozone with the (100) plane of solid potassium iodide (KI) was investigated using atomic force microscopy (AFM). The reaction forming potassium iodate (KIO3) initiates at step edges prior to reacting on the flat terraces. Small domains of KIO3, initially 3.8 Å in height, are formed on the top of step edges. Following reaction at the step edge, domains of KIO3 are formed across the terraces. With prolonged exposure to ozone, KIO3 domains nucleate further growth until the surface is evenly covered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 18 publications
(38 reference statements)
2
29
1
Order By: Relevance
“…(1): It is noted that the oxidation of KI to form KIO 3 (as shown in Eq. (2) is unlikely to occur during the sampling period because its progression requires a relatively dry environment (Brown et al, 2008).…”
Section: Collection Efficiencymentioning
confidence: 99%
“…(1): It is noted that the oxidation of KI to form KIO 3 (as shown in Eq. (2) is unlikely to occur during the sampling period because its progression requires a relatively dry environment (Brown et al, 2008).…”
Section: Collection Efficiencymentioning
confidence: 99%
“…Further oxidation leads to passivation by KIO 3 , with oxide crystallites 4-6 nm in height and 10-30 nm in width. 24 Figure 3 shows AFM images after a passivated KIO 3 oxide layer is exposed to 65% relative humidity for 1 h. The water vapor content of the cell was removed by flowing dry nitrogen prior to imaging. After exposure to 65% relative humidity for 1 h, the surface loses its roughness and large stepless terraces are regenerated.…”
Section: X-ray Photoemission Spectroscopy (Xps)mentioning
confidence: 99%
“…Some ions accumulate at a specific depth layer of water–hydrophobes (e.g., air, oil, and biomembranes) interfaces, while other ions prefer to remain in bulk water and react homogeneously. Long-chain carboxylate ions, due to the amphiphilic property, play key roles in the nucleation, growth, and photochemical aging process of atmospheric aerosol. For example, bubble-bursting from surface of the ocean is responsible for enriching marine aerosols with long-chain carboxylate ions, ,,, thereby influencing the chemistry of marine boundary layers. , Long-chain carboxylate ions act as a film covering atmospheric particles, directly confirmed by field measurement studies. Recent studies have suggested long-chain carboxylate ions could induce cloud droplet formation, thereby affecting global climate change. , Benzoate ion, C 6 H 5 -COO – , has been recently found to be one of the most abundant organic species observed in PM 2.5 of polluted areas, where the concentration on PM 2.5 exceeds 1 μg/m 3 …”
Section: Introductionmentioning
confidence: 99%